2019
DOI: 10.1097/sla.0000000000003659
|View full text |Cite
|
Sign up to set email alerts
|

International Validation of Reduced Major Morbidity After Minimally Invasive Distal Pancreatectomy Compared With Open Pancreatectomy

Abstract: in collaboration with the Dutch Pancreatic Cancer GroupObjective: To quantify the nationwide impact of minimally invasive distal pancreatectomy (MIDP) on major morbidity as compared with open distal pancreatectomy (ODP). Background: A recent randomized controlled trial (RCT) demonstrated significant reduction in time to functional recovery after MIDP compared with ODP, but was not powered to assess potential risk reductions in major morbidity. Methods: International cohort study using the American College of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…Furthermore, no patients in the RTP group were converted to an open procedure. A recent study showed that conversion rates in minimally invasive pancreatic surgery are improving and appear to be significantly lower in robotic cases (50). It appears that precision in instrument movement and tissue manipulation achieved with the robot is crucial in that aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no patients in the RTP group were converted to an open procedure. A recent study showed that conversion rates in minimally invasive pancreatic surgery are improving and appear to be significantly lower in robotic cases (50). It appears that precision in instrument movement and tissue manipulation achieved with the robot is crucial in that aspect.…”
Section: Discussionmentioning
confidence: 99%
“…25 Studies have shown that LDP offers several advantages over open surgery, especially in short-term perioperative outcomes including less postoperative pain, quicker recovery and decreased blood loss. [12][13][14]26,27 However, most of these studies were retrospective case-control series. In the only RCT (LEOPARD) that compared minimally invasive DP and open DP by the Dutch Pancreatic Cancer Group, Rooij et al found that the former was significantly associated with decreased blood loss and reduced time to functional recovery at the expense of longer operating time.…”
Section: Distal Pancreatectomymentioning
confidence: 99%
“…21 Similarly, a recent large international cohort study that analysed 1562 minimally invasive DP with 18% open conversion vs 1359 open DP from the American College of Surgeons National Quality Improvement Program demonstrated a risk reduction rate of 11% in composite major morbidity. 27 Although DP is commonly performed with en bloc splenectomy, recent studies have recommended spleen preservation since it reduces the risk of postsplenectomy infection and thrombocytosis, haematologic abnormalities and overall morbidity. 28,29 Most pancreatic surgeons concur that the spleen should be preserved as far as possible in benign and borderline malignant neoplasms, 5,22 and 2 techniques have been described for spleen-preserving DP: 1) in the Warshaw technique, the splenic artery and vein are resected, leaving only the short gastric vessels for perfusion of the spleen; and 2) in the Kimura technique, the splenic vessels are spared.…”
Section: Distal Pancreatectomymentioning
confidence: 99%
See 1 more Smart Citation
“…They performed appropriate adjustments for the confounding factors by indication. Their results suggested that MIDP was independently associated with reduced composite major morbidity, which includes death and severe complications [17]. With robotic-assisted procedures, a significant increase in the frequency of resections was performed for asymptomatic tumors.…”
Section: Introductionmentioning
confidence: 99%